Music Teachers' Perceptions of, and approaches to, Creativity in the Greek‐Cypriot Primary Education. (2nd August 2021) - Makris, Stavros; Welch, Graham F.; Himonides, Evangelos
Abstract: The purpose of this study was to explore music teachers' perceptions of, and approaches to, creativity in Primary education. Even though teachers' perceptions on creativity have been investigated broadly and extensively, qualitative research on music teachers' beliefs nurturing the students' creativity in Primary education are less common. In the present paper, data were collected through in‐depth interviews with 10 individuals in the Greek‐Cypriot Primary Education. The results of this exploratory study indicated that activities should include the promotion of the students' self‐action and autonomy, and the pedagogical initiatives that enable students to come up with original outputs in order to be creative. This understanding, in turn, provided the researchers with access to the teacher participants' perceptions of creativity: a multifaceted concept related to students' autonomy, initiative, and the application of imagination and unrestrained thinking to any musical activity. These findings offer some initial insights and are discussed with respect to their implications for policy and practice. Suggestions for future research are also made.